EFEKTIVITAS DAUN SIRIH MERAH (Piper crocatum) PADA SANITASI DI RUANG PENAMPUNGAN SUSU - Eulis Tanti Marlina; Ellin Harlia; Yuli Astuti Hidayati; Deden Zamzam Badruzzaman (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Red betel is a multipurpose plant, because apart from being an ornamental plant, because of the beauty of its leaves, it also has several active compounds as antibacterial agents. The aim of this research was to study the effectiveness of red betel leaf extract as a natural disinfectant in the milk storage room through its inhibitory power against bacteria in situ and its effect on reducing the number of total bacteria on the floor, table, and walls in the milk storage room. The research used experimental method using completely randomized design with 3 treatments of red betel leaf extract concentration, P1 = 15%, P2 = 25%, P3 = 35%, each treatment was repeated 6 times. The research data were analyzed using analysis of variance and Tukey's test. The results showed that the highest reduction in the total number of bacteria was in the red betel leaf extract with a concentration of 35%, both on the floor, table, and walls in the milk storage room, respectively 52.40%, 59.96%, and 61.77%. The inhibition zone of red betel leaf extract against bacteria in situ was the highest at a concentration of 35% red betel leaf extract on the floor, table and wall, namely 9.12; 10.65; and 10.76 mm.